Ternary copper molybdenum sulfide (Cu2MoS4) nanoparticles anchored on PANI/rGO as electrocatalysts for oxygen evolution reaction (OER). (10th April 2022) - Singh, Ayushi; Singh, Amita; Kociok‐Köhn, Gabriele; Bhimireddi, Rajasekhar; Singh, Anar; Singh, Ashish Kumar; Kumar, Abhinav; Muddassir, Mohd.
Abstract : A trinuclear heterobimetallic complex with general formula [Cu(PPh3 )S2 MoS2 Cu(PPh3 )2 ]·CHCl3 (SSP ) has been synthesized, and its characterization executed using FTIR, NMR, electronic absorption spectroscopies, and single‐crystal X‐ray technique. The complex is solvothermally decomposed in octadecylamine (ODA) to yield ternary copper molybdenum sulfide nanoparticles and successfully grafted onto 2D materials, namely, reduced graphene oxide (rGO) or polyaniline (PANI), and these composites are utilized for oxygen evolution half‐cell reaction (OER). The copper molybdenum sulfide nanoparticles as well as their composites with rGO and PANI and rGO + PANI were characterized using powder X‐ray diffraction, SEM, and EDX analyses. Electrochemical measurements suggested that the modified electrodes have notable electrocatalytic activity toward OER with onset overpotential 400 mV for CMS  + PANI and 395 mV for CMS  + rGO + PANI. This is the first study on the use of copper molybdenum sulfide nanoparticles composites with rGO and PANI as electrocatalysts for OER displaying substantial synergistic activity. Abstract : Atrinuclear complex [Cu(PPh3 )S2 MoS2 Cu(PPh3 )2 ] synthesized and its decomposed product and its composites used as electrocatalysts for OER.